2013
DOI: 10.1080/02763869.2013.749134
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use at a University Health Science Center

Abstract: This article describes the results of a survey of library patrons conducted by librarians and information technology specialists at the Health Science Center Libraries at the University of Florida. The purpose of the survey was to learn if and how library patrons were using smartphones to perform their work-related tasks and how patrons felt the library could support smartphone use at the Health Science Center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…In a health sciences centre, accessing drug information resources was the most frequent answer to the question "what work-related tasks would you like to be able to perform?" [10]. Our study provides a more in-depth look at the types of drug information sought by pharmacy students and faculty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a health sciences centre, accessing drug information resources was the most frequent answer to the question "what work-related tasks would you like to be able to perform?" [10]. Our study provides a more in-depth look at the types of drug information sought by pharmacy students and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…While some resources have been made freely available, others must be purchased by individuals and some have been institutionally licensed by libraries. Bushhousen et al [10] noted a desire from patrons to have libraries serve as a clearinghouse of vetted smartphone applications and services, but there are several challenges involved in providing mobile device and application support to library users. These include: limited availability of products that can be institutionally licensed for mobile devices, the often complex authentication processes involved in accessing those products, the large number of mobile software platforms that require support, as well as the often very high annual costs for subscribing to these products [21].…”
Section: Introductionmentioning
confidence: 99%
“…The students felt that their ability to use the devices was restricted by a lack of instruction on the specific apps, however they were eager to use the devices because they were required by the medical programs that they were enrolled in. The team of researchers and technology specialists found that education on app use was high on the list of required services by their patrons (Bushhousen et al, 2013).…”
Section: Device Ownership and Barriers To Usementioning
confidence: 99%
“…For example, Bushhousen et al (2013) asked health sciences library patrons about potential use and perceived barriers. The students felt that their ability to use the devices was restricted by a lack of instruction on the specific apps, however they were eager to use the devices because they were required by the medical programs that they were enrolled in.…”
Section: Device Ownership and Barriers To Usementioning
confidence: 99%
“…The recent health sciences library literature explores many facets of this rapid and increasing change. Advances in technology have brought both new opportunities and new demands to health sciences libraries as seen with mobile resources [7,8] and web 2.0 and social networking [9,10]. Library staffing and space have been affected by fluctuating budgets and shifts to predominantly electronic resources and collections [ 11Á 13].…”
Section: Introductionmentioning
confidence: 99%